EFEKTIVITAS PELATIHAN PENGGUNAAN MIKROSKOP UNTUK PENGUATAN PRAKTIKUM BIOLOGI SISWA SMA NEGERI 8 KOTA TERNATE - Nurhasanah Nurhasanah; Suparman Suparman; Nurmaya Papuangan; Rosihan Turuy; Miftakhul Khasanah; Hamida Higoro; Murni Talib (Jurnal Abdi Insani, 2026)
Microscope skills are fundamental in biology education as they connect theoretical concepts with direct observation of cells and tissues. However, many students still struggle to operate microscopes properly, resulting in suboptimal practical sessions. This activity aimed to enhance students’ understanding and practical skills through structured microscope training. The training was conducted on May 18, 2025, at SMA Negeri 8 Ternate, involving 42 eleventh-grade students (20 males and 22 females) and three biology teachers. The program included theoretical explanation, demonstration, and hands-on practice using the cyanoacrylate-based leaf epidermis replica technique. Training effectiveness was evaluated through pre-test and post-test scores, practical skill rubrics, and participant satisfaction questionnaires. The training significantly improved students’ learning outcomes. The average knowledge score increased by 24.5% (from 59.8 to 84.3), while practical skills reached an average of 81.5% (“good” category). Participant satisfaction averaged 88%, with the highest ratings on clarity of instruction (3.6) and opportunity for discussion (3.7). Attendance (92%) and engagement in practice (91%) reflected high enthusiasm and active participation. These findings indicate that structured, hands-on training supported by repeated practice and interactive facilitation effectively enhances both conceptual and procedural competencies in microscopy. The model also promotes collaboration and strengthens students’ scientific skills. Microscope training at SMA Negeri 8 Ternate proved effective in improving students’ knowledge, skills, and motivation. This training model is recommended for broader application to strengthen biology practicum competencies and can be adapted for other school laboratory topics.